2014
DOI: 10.1063/1.4886387
|View full text |Cite
|
Sign up to set email alerts
|

Upgrades of imaging x-ray crystal spectrometers for high-resolution and high-temperature plasma diagnostics on EAST

Abstract: Upgrade of the imaging X-ray crystal spectrometers continues in order to fulfill the high-performance diagnostics requirements on EAST. For the tangential spectrometer, a new large pixelated two-dimensional detector was deployed on tokamaks for time-resolved X-ray imaging. This vacuum-compatible detector has an area of 83.8 × 325.3 mm(2), a framing rate over 150 Hz, and water-cooling capability for long-pulse discharges. To effectively extend the temperature limit, a double-crystal assembly was designed to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…The additional heating powers from lower hybrid current drive (LHCD) P LHCD ¼ 3 MW and ion cyclotron radio frequency (ICRF)P ICRF ¼ 1.4 MW keep constant. The toroidal rotation near the plasma center is very close to 0 (<4 krad=s) measured by x-ray crystal image spectrometry (XCIS) [20]. The toroidal field strength B T ¼ 2…”
mentioning
confidence: 99%
“…The additional heating powers from lower hybrid current drive (LHCD) P LHCD ¼ 3 MW and ion cyclotron radio frequency (ICRF)P ICRF ¼ 1.4 MW keep constant. The toroidal rotation near the plasma center is very close to 0 (<4 krad=s) measured by x-ray crystal image spectrometry (XCIS) [20]. The toroidal field strength B T ¼ 2…”
mentioning
confidence: 99%
“…The mitigation of high- Z impurity emissions seems to be related to rather than to variations in , or which only change modestly. Even the spatial profiles of , from the TS diagnostic (Zang et al 2010) and from XCS (Lyu et al 2014, 2016), shown in figure 4, do not appear to account for the mitigation levels, with , slightly increasing with RMP (particularly more so in central plasma regions) and staying relatively the same.
Figure 4.Changes of profiles of , (from the TS diagnostic) and (from XCS) at (before RMP, black coloured) and at (during RMP, blue coloured).
…”
Section: Experimental Data Acquisitionmentioning
confidence: 98%
“…in active spectral (red lines) are in excellent agreement with passive ones (blue lines), beam modulation method is reliable. The core ion temperature is about 1.1 keV obtained by X-ray crystal spectrometer; 13 thus, the halo's thermal broadening is about 1.2 nm. The roughly calculated halo matches the net signal (green lines) well; the FIDA signal and halo can be separated with the employment of FIDASIM.…”
Section: Instrument Performancementioning
confidence: 99%